Fabrication of superconducting coils and (Ba, A)Fe2As2 (A:Na, K) long round wires with large superconducting cores. Issue 1 (1st August 2022) - Pyon, S; Ito, T; Tamegai, T; Kajitani, H; Koizumi, N; Awaji, S; Kito, H; Ishida, S; Yoshida, Y
Abstract: We fabricated superconducting coils using 10-20 m-class round wires of 122-type iron-based superconductors (IBSs). Round wires and coils are fabricated by powder-in-tube method and hot-isostatic-press technique. Transport critical current ( I c ) of the whole (Ba, K)Fe2 As2 coil is 46 A under the self-field at 4.2 K, and magnetic field at the center of the coil reaches 0.3 T. Although the edge of the long wire in the coil is damaged, the rest of the part is relatively homogeneous. Furthermore, the largest transport critical current density ( J c ) and I c in (Ba, K)Fe2 As2 wires picked up from the coil reach 49 kAcm −2 and 44 A at 4.2 K under a magnetic field of 10 T, respectively. This value exceeds the previous highest transport J c of (Ba, K)Fe2 As2 round wires. We also fabricated a (Ba, Na)Fe2 As2 coil using long round wire with large superconducting core by react and wind method. Transport I c of the coil is significantly low due to cracks perpendicular to electric current flow direction, although magnetic J c in the round wire picked up from the coil reaches 40 kAcm −2 at 4.2 K under 4 T.